Functional Properties and Antioxidant Activity of Morus alba L. Leaves var. Zolwinska Wielkolistna (WML-P)-The Effect of Controlled Conditioning Process - Monika Przeor; Ewa Flaczyk; Dominik Kmiecik; Maciej S. Buchowski; Halina Staniek; Aneta Tomczak-Graczyk; Joanna Kobus-Cisowska; Anna Gramza-Michałowska; Joanna Foksowicz-Flaczyk (MDPI AG, 2020)
This study evaluated the effect of adding a new step, termed conditioning, to the traditional processing of leaves from Morus alba var. zolwinska wielkolistna grown in Poland (WML-P). This step, modeled on tea leaves processing, was conducted in a controlled environment on a semi-technical scale. The primary goal was to evaluate the effect of the WML-P conditioning for 1-4 h at 32-35 °C on the content of bioactive compounds (total phenolics, phenolic acids, flavonols, 1-deoxynojirimycin) and antioxidant activity (radical scavenging against DPPH, antioxidant capacity, chelating activity and ferric reducing antioxidant potential) of the lyophilized extracts. For the first time WML-P extracts content was comprehensively characterized by assessing dietary fiber fractions, fatty acids, amino acids, macro- and microelements and chlorophyll content. Compared to the traditional process, adding the conditioning step to WML-P processing resulted in an increased total phenolics content, radical scavenging capacity, ability to quench 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and iron-chelating ability in the lyophilized extracts. The beneficial effect depended on conditioning time. The highest flavonols and phenolic acids content were found after 2-h conditioning. We concluded that adding a 2-h conditioning step to traditional WML-P processing results in getting WML-P lyophilized extract with increased bioactive compounds content and high antioxidant activity.